2023
DOI: 10.1186/s13089-023-00322-9
|View full text |Cite
|
Sign up to set email alerts
|

Intra-and inter-observer variability of point of care ultrasound measurements to evaluate hemodynamic parameters in healthy volunteers

Abstract: Background Point-of-care ultrasound (POCUS) is a valuable tool for assessing the hemodynamic status of acute patients. Even though POCUS often uses a qualitative approach, quantitative measurements have potential advantages in evaluating hemodynamic status. Several quantitative ultrasound parameters can be used to assess the hemodynamic status and cardiac function. However, only limited data on the feasibility and reliability of the quantitative hemodynamic measurements in the point-of-care set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…We found substantial IRR for the VExUS score between multiple readers and IUR between images acquired from the same patient by sequential ultrasonographers. The IRR of the VExUS exam as collected and interpreted by physicians was superior the reported IRR of IVC measurement in a group of emergency department physicians [ 15 ], and similar to the IRR of IVC measurements when collected by professional ultrasonographers [ 16 ]. Though substantial, the KS for the VExUS grade was lower than reported in a recent study of VExUS in patients with septic shock, which reported a KS of 0.95 (95% CI 0.90–1.0) between two experts [ 17 ].…”
Section: Discussionmentioning
confidence: 72%
“…We found substantial IRR for the VExUS score between multiple readers and IUR between images acquired from the same patient by sequential ultrasonographers. The IRR of the VExUS exam as collected and interpreted by physicians was superior the reported IRR of IVC measurement in a group of emergency department physicians [ 15 ], and similar to the IRR of IVC measurements when collected by professional ultrasonographers [ 16 ]. Though substantial, the KS for the VExUS grade was lower than reported in a recent study of VExUS in patients with septic shock, which reported a KS of 0.95 (95% CI 0.90–1.0) between two experts [ 17 ].…”
Section: Discussionmentioning
confidence: 72%
“…Given the very low CV, [ 11 ] this work also demonstrates the repeatability of pleural thickness measurement using high-frequency ultrasound. This can be interesting as these probes have higher superficial resolution and can be used for the same purpose in adults too.…”
mentioning
confidence: 84%
“…A CV of less than 10% was considered as low data dispersion (i.e. : good repeatability), as previously published [ 11 ]. As this was the first study of its kind, a formal sample size calculation was unfeasible and we choose a convenience sample size of 100 neonates, which was larger than the unique preliminary neonatal study available [ 5 ].…”
mentioning
confidence: 99%
“…ABI does not assess the microcirculation, and ABIs do not correlate with the degree of MVD [ 22 , 23 ]. In terms of imaging, duplex Doppler and computed tomography (CT) angiography are frequently used to assess PAD anatomy and severity, and while these approaches offer a reasonable assessment of large vessel anatomy, they do not assess microcirculation under standard protocols [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%